Team Game Tournament Cooperative Learning Model Based on Problem Solving Impact on Collaboration Ability and Learning Outcomes - I Gusti Ayu Sri Trisna Dewi; I Wayan Lasmawan; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2024)
The low collaboration ability and learning outcomes of Pancasila Education are caused by the appropriate learning model and the learning method is still rote memorization. The purpose of this research is to determine the differences in student learning collaboration skills between groups of students taught with the TGT learning model and groups of students taught with the conventional learning model, differences in Pancasila education learning outcomes between groups of students taught with the TGT learning model and groups of students taught with conventional learning model, differences in collaboration skills and Pancasika education learning outcomes between groups of students taught using the TGT learning model and groups of students taught using the conventional learning model. This type of research is quasi-experimental research. The research design used was post-test only control group design. Data collection methods use test and non-test techniques. Data were analyzed using Manova. The research results showed that there was a significant influence of the problem-solving-based TGT learning model on collaboration skills and Pancasila Education learning outcomes. With the TGT learning model, students get direct learning experience so that learning is more interesting and can improve collaboration skills and student learning outcomes. From the data, it is recommended that teachers use the TGT learning model in teaching Pancasila education in elementary schools to improve collaboration skills and student learning outcomes.